Antiangiogenic therapy of age-related degeneration of the macula (Ukrainian Journal of Ophthalmology, 2026)
Antiangiogenic therapy of age-related degeneration of the macula
Keywords: age-related macular degeneration; vascular endothelial growth factor inhibitor; ranibizumab; aflibercept; bevacizumab